2001
DOI: 10.1152/ajpregu.2001.280.2.r527
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 17β-estradiol on levels and distribution of metallothionein and zinc in squirrelfish

Abstract: Females of the squirrelfish family (Holocentridae) accumulate higher levels of zinc in the liver than any other known animal. This zinc accumulation is made possible by high expression of the zinc-binding protein, metallothionein (MT). In the present study, the squirrelfish (Holocentrus ascensionis) MT cDNA was cloned and sequenced. The deduced amino acid sequence was very similar to other teleost MT. The role of estrogens on zinc metabolism was investigated by injecting male and immature female squirrelfish w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…However, also in rats, Nishiyama et al (1988) observed that pretreatment with E 2 directly increased the accumulation of Cd 2+ into the renal cells without inducing the synthesis of MTs. In females of the squirrelfish family (Holocentridae), E 2 did not directly alter the levels of zinc or MT mRNA in the liver (Thompson et al 2001). However, the hepatic MT protein concentration increased differentially in the nuclear fraction.…”
Section: Discussionmentioning
confidence: 97%
“…However, also in rats, Nishiyama et al (1988) observed that pretreatment with E 2 directly increased the accumulation of Cd 2+ into the renal cells without inducing the synthesis of MTs. In females of the squirrelfish family (Holocentridae), E 2 did not directly alter the levels of zinc or MT mRNA in the liver (Thompson et al 2001). However, the hepatic MT protein concentration increased differentially in the nuclear fraction.…”
Section: Discussionmentioning
confidence: 97%
“…In the parallel experiment, we observed a significant increase in vg expression in carp treated with 17b-estradiol, with no changes in mt expression. In other species like Salvelinus namaycush (Werner et al, 2006) and Holocentrus ascensionis (Thompson et al, 2001), crosstalk was described between heavy metal and estrogen response pathways in experimental conditions implying waterborne exposure or immature fish. Although in our experiments no significant difference of the response of mt to estrogen or vg to Zn was detected, we cannot completely exclude that there might exist a cross-reaction to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…The primary antibody was a rabbit anti-turtle VTG IgG diluted 1∶10000 in TBS-T. The cross-reactivity of this antibody with squirrelfish VTG has been documented previously [7]. The secondary antibody was a horseradish peroxidase-linked donkey anti-sheep IgG (BioRad) diluted 1∶40000 in TBS-T.…”
Section: Methodsmentioning
confidence: 99%
“…In individual females with high hepatic Zn levels, MT was estimated to constitute 35% (w/w) of all hepatic proteins [5], [6]. Previous findings suggest that the MT protein sequence deduced from squirrelfish MT cDNA is very similar to that of other vertebrates [7]. Thus, it is unlikely that Zn accumulation in female squirrelfish liver is caused by an atypical MT structure.…”
Section: Introductionmentioning
confidence: 99%